Baseline composition, quantity, and condition of bycatch in the southern Gulf of St. Lawrence spring and summer American lobster fisheries - Stephanie A. Boudreau; Patricia H. Hanley (FACETS, 2023)
The impact of the southern Gulf of St. Lawrence American lobster (Homarus americanus) fishery on species bycatch is currently unknown. The composition of the incidental catch, both nonharvestable lobster (by fisheries regulations) and nonlobster species, was systematically collected over the 2015 spring and summer fishing seasons. A total of 51 948 (7147 were nonlobster taxa) individual organisms weighing 13 987.60 kg (1223.91 kg of nonlobster taxa) were captured as bycatch during 73 fishing trips. By weight per trip, the most common lobster bycatch were undersized male and females, and the highest nonlobster species catch were Atlantic rock crab (Cancer irroratus). A semiquantitative assessment of injury and vitality was applied to bycatch as a proxy for discard mortality. The majority of the individuals assessed for visible injury were deemed uninjured (98% both fish and invertebrates); however, postrelease mortality was not measured. A smaller study in 2019 corroborated the 2015 catches and supported current assumptions that the passive gear type, the low diversity of bycatch, and the rapid hand-sorting of the trap minimize the impact of the lobster fishery on incidentally captured taxa. Further scientific monitoring is recommended to better account for all sources of mortality in stock assessments and rebuilding plans.